Social capital and mental health status among the residents of a neighborhood in Istanbul, Turkey. (13th November 2019) - Kayi, I; Ozgulnar, N
Abstract: : There has been an increasing policy making and research for social determinants of health and inequalities in health. In such a framework social capital functions as an intermediate factor at the and it is increasingly investigated in health research. Social capital is defined as a resource that individuals may access through membership in a structure of network with certain values and through sharing these resources reciprocally. The objective of this study is to investigate the association between social capital and mental health status among residents of a small neighborhood on Istanbul. This is a cross-sectional study that has been carried out in Istanbul with individuals of age 18-65 years old. The study sample included 629 individuals selected by a stratified and systematic sampling process. Data was collected via a self-reported questionnaire including items for sociodemographic information, social capital and General Health Questionnaire. We applied Mann-Whitney U and Kruskal-Wallis Tests subsequent to the normality tests of the distribution, and Chi Square Test for the categorical data. Linear and logistic regression models were used for multivariable analysis. Men constitute 51.7% of the people. Mean age was 40.1 (sd: 12.7). There was a significant association between social capital and being a woman and deprived neighborhood. In addition higher level of mental distress was significantly associated with lower level of neighborhood trust, social support and the higher level of perception that neighbors would take advantage of the participants when they got the chance. However national level trust and sense of people taking advantage of their neighbors were not significantly associated with mental health status. Social capital measured via trust and social support at the neighborhood level has been a determinant of mental health status. Efforts for decreasing socioeconomic inequalities should also include efforts to promote social capital. Key messages: Social capital measured via trust and social support at the neighborhood level has been a determinant of mental health status. Efforts for decreasing socioeconomic inequalities should also include efforts to promote social capital.